Analisis Kinerja Keuangan Pada Toko Photo Copy dan Alat Tulis Bulpa Jaya Mandiri - Fauziah Fauziah; Desmawati Desmawati (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The company's financial performance is the result of many individual decisions that are made continuously by management. Therefore to assess the financial performance of a company, it is necessary to involve an analysis of the cumulative and economic financial impacts of decisions and consider them using a comparative measure. Analysis carried out is limited to information from Bulpa Jaya Mandiri Copy and Stationery from 2016 to 2018, to assess the condition of financial performance presented in the financial statements including the balance sheet, income statement and changes in financial position, but for the purpose of this analysis use more balance sheets and income statement statement. To find out the condition of financial performance, several analytical tools are needed, including liquidity ratios, solvency ratios, activity ratios and profitability ratios. When compared with the standard financial soundness criterion, the figure below 30% indicates the financial condition and financial soundness of the Bulpa Jaya photocopy shop independently and unhealthy, with a poor value. This means that the ability of Bulpa Jaya Mandiri photo copy shops is 17.82% of the owner's capital.